Patient Benefit-Risk Tradeoffs for Radioactive Iodine-Refractory Differentiated Thyroid Cancer Treatments. (30th November 2015) - Mohamed, Ateesha F.; González, Juan Marcos; Fairchild, Angelyn
Abstract : Background . The aims of this study were to assess patients' preferences to wait or start systemic treatment and understand how patients would make tradeoffs between certain severe adverse events (AEs) and additional months of progression-free survival (PFS). Materials and Methods . Adults in France, Germany, and Spain with a diagnosis of DTC and who have had at least one RAI treatment completed a direct-elicitation question and a discrete-choice experiment (DCE) online. The direct-elicitation question asked respondents whether they would opt out of treatment when their tumor is RAI-R. In the DCE, respondents chose between 12 pairs of hypothetical RAI-R DTC treatment profiles. Profiles were defined by magnitudes of efficacy (PFS) and safety (severe hand-foot skin reaction [HFSR], severe proteinuria, and severe hypertension). A main-effects random-parameters logit model was estimated. Results . 134 patients completed the survey. Most patients (86.6%) opted for treatment rather than "wait and see" decision. Patients placed a greater weight on the risk of severe hypertension than the risk of proteinuria and HFSR. Conclusions . DTC patients showed preference toward treatment for RAI-R DTC over watchful waiting. Patients' concerns about the risk of severe hypertension appeared to have had a greater effect on patients' choice than severe proteinuria or HFSR.